The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.colsurfb.2015.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Silk structure and degradation

Abstract: To investigate the structure of silk and its degradation properties, we have monitored the structure of silk using scanning electron microscopy and frozen sections. Raw silk and degummed raw silk were immersed in four types of degradation solutions for 156 d to observe their degradation properties. The subcutaneous implants in rats were removed after 7, 14, 56, 84, 129, and 145 d for frozen sectioning and subsequent staining with hematoxylin and eosin (H.E.), DAPI, Beta-actin and Collagen I immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 26 publications
(82 reference statements)
1
78
0
Order By: Relevance
“…Silk from silkworms is composed of two primary proteins: SF (approximately 75%) and sericin (approximately 25%) (Figure 1) [22]. In raw silk, sericin is positioned across the surface of two parallel fibroin fibers, binding them together.…”
Section: Physicochemical Properties Of Silk Fibroin As Biomaterialsmentioning
confidence: 99%
“…Silk from silkworms is composed of two primary proteins: SF (approximately 75%) and sericin (approximately 25%) (Figure 1) [22]. In raw silk, sericin is positioned across the surface of two parallel fibroin fibers, binding them together.…”
Section: Physicochemical Properties Of Silk Fibroin As Biomaterialsmentioning
confidence: 99%
“…Compared to the previously reported bioresorbable polyester polymers, silk‐based natural peptide fibers (naturally produced by Bombyx mori larvae) have been reported as a more attractive alternative for the design of bioresorbable sensors and electronics because of the robust mechanical properties, the ability to tailor dissolution and biodegradation rates (from hours to years), the formation of noninflammatory amino acid degradation products, and the option to prepare the materials at ambient conditions to preserve sensitive electronic functions . From the chemical point of view, silk consists of two main proteins, namely, sericin and fibroin, the latter being the structural center of the silk, while the former being the sticky material surrounding it.…”
Section: Bioresorbable Materials and Dissolution Chemistrymentioning
confidence: 99%
“…From the chemical point of view, silk consists of two main proteins, namely, sericin and fibroin, the latter being the structural center of the silk, while the former being the sticky material surrounding it. In vitro dissolution tests of raw silk and of fibroin and sericin filaments (PBS at 37 °C) showed that dissolution occurred with weight losses of 0.12 and 0.08% day −1 , respectively …”
Section: Bioresorbable Materials and Dissolution Chemistrymentioning
confidence: 99%
“…Complete removal of sericin from the fibroin fibers is the key step in insuring the material's biocompatibility. Neither fibroin or sericin elicit an immune response when isolated, but when combined there is an inflammatory reaction (Jiao et al, 2017;Liu et al, 2015;Mandal, Priya, & Kundu, 2009;Panilaitis et al, 2003;Thurber et al, 2015). Silk fibroin has proven that it outperforms the leading polymer scaffolding materials in biocompatibility and has been shown to cause minimal immunogenic effects on a number of cell types, including peripheral nerve ganglia (Yang et al, 2007), fibroblasts (Boonrungsiman et al, 2018), and chondrocytes (D. K. Kim, In Kim, Sim, & Khang, 2017;Talukdar et al, 2011).…”
Section: Biocompatibilitymentioning
confidence: 99%